Evaluasi Kelayakan Bahan Ajar Teks Cerita Inspiratif Bermuatan Nilai-nilai Kepemimpinan Berbantuan Media Digital Interaktif di SMP - Desiani, Khoirunnisa Mei; Harahap, Rosmawaty; Dalimunthe, Syairal Fahmy (Jurnal Bahasa dan Sastra, 2024)
This study evaluates the feasibility of using interactive digital media to teach inspirational story texts that promote leadership values in middle school. The researcher has played a direct role in the planning process, data collection, data analysis, data interpretation, and data conclusion. The participants included Postgraduate lecturers from Medan State University, Bahasa Indonesia teachers, and a total of 43 middle school students. The data collection technique used in this study was a researcher's instrument, specifically a questionnaire to assess the developed product. The results showed that the teaching materials, which combined inspirational story texts and interactive digital media, scored an average of 82.35% in terms of content eligibility, indicating an “excellent” rating. Language proficiency received an average score of 81.73% with an “excellent” rating, while presentability scored an average of 86.45% with an "excellent" rating. Graphics feasibility received an average score of 90% with an “excellent” rating. Teacher assessments averaged a score of 95, also indicating an "excellent" rating. The small group test scores received an average of 84.12 with an “excellent” rating, and the large group trial scores averaged 91.03 with an “excellent” rating. Overall, the findings suggest that the use of interactive digital media to teach inspirational story texts that promote leadership values in middle school is highly recommended, as it received an overall rating of “excellent”.